Changes in Training, Lifestyle, Psychological and Demographic Factors, and Associations With Running-Related Injuries During COVID-19 - Holmes, Hillary H.; Monaghan, Patrick G.; Strunk, Kamden K.; Paquette, Max R.; Roper, Jaimie A. (Frontiers in Sports and Active Living, 2021)
The purpose of this study was to examine how the type and magnitude of changes in running behavior influence running related injuries. We also examined how lifestyle and psychosocial wellness measures may influence running behavior change. An online survey was distributed to individuals over the age of 18 that currently run or have previously ran for exercise. The survey included questions examining injury details, training-related changes, environment-related changes, social-related changes, and psychosocial wellness. Changes reflected differences in running behaviors prior to COVID-19 restrictions and during COVID-19 restrictions. A total of 1035 runners were included in analysis. Injuries were sustained in 9.5% of runners. Injured runners made a greater number of total changes (p = .031) as well as training-related (p = .042) and environment-related (p = .017) changes compared to injured runners. A significant relationship was found between injury and those that reported less time to exercise to changes in work environment (p =.017). This study highlights the multi-dimensional nature of running-related injuries and the need to consider the interaction of multiple changes in running behavior, rather than isolating single factors. Greater understanding of the underlying causes of running related injuries can help reduce the risk of future injury.